Successful pregnancy located in a uterine cesarean scar: A case report - Shoko Tamada; Hisashi Masuyama; Jota Maki; Takeshi Eguchi; Takashi Mitsui; Eriko Eto; Kei Hayata; Yuji Hiramatsu (Elsevier, 2017)
Cesarean scar pregnancy (CSP) is a rare form of ectopic pregnancy. Because CSP carries a high risk of uterine rupture and life-threatening bleeding, the pregnancy should be terminated upon confirmation of diagnosis. There have been few reports of CSP with successful delivery. We present a case of CSP under expectant management, with delivery via planned cesarean section at 35 weeks of gestation. This report suggests that successful pregnancy outcome can be achieved in some women with uterine cesarean scar, but further analysis and additional studies are required in order to describe the optimal protocol of expectant management in CSP.